Laparoendoscopic management of gastric duplication: case report - Salazar Tantaleán, Víctor Augusto (2024)
Introduction: Gastric duplication is a rare congenital pathology that is often incidental. Case of report: In this case, the case of a gastric duplication in a young patient evaluated and treated in the public hospital, who comes for repetitive episodes of abdominal pain and vomiting. In the preoperative period, endoscopic and non-contributory imaging studies were studied. Subsequently he underwent a laparoscopic surgical treatment with favorable evolution. The pathological study determined the definitive diagnosis. Conclusion: The laparoscopic approach is suitable for the management of GD as it is associated with fewer postoperative complications; Likewise, the joint use of echoendoscopy allows us to delimit the morphology and location of the lesion.